2012
DOI: 10.1123/japa.20.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Gardening as a Potential Activity to Reduce Falls in Older Adults

Abstract: This study examines whether participation in gardening predicts reduced fall risk and performance on balance and gait-speed measures in older adults. Data on adults age 65 and older (N = 3,237) from the Health and Retirement Study and Consumption and Activities Mail Survey were analyzed. Participants who spent 1 hr or more gardening in the past week were defined as gardeners, resulting in a total of 1,585 gardeners and 1,652 nongardeners. Independent t tests, chi square, and regression analyses were conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 63 publications
1
43
0
1
Order By: Relevance
“…Chen and Janke (2012) reported that participation in SGs contributed to the prevention of falls, whereas Detweiler, Murphy, Kim, Myers, and Ashai (2009) reported that the introduction of a SG was associated with a reduction in the frequency of falls in general, particularly serious falls. Improved knowledge of research findings and how to prevent falls might improve the clinical practice regarding this issue.…”
Section: Physical Activitymentioning
confidence: 97%
“…Chen and Janke (2012) reported that participation in SGs contributed to the prevention of falls, whereas Detweiler, Murphy, Kim, Myers, and Ashai (2009) reported that the introduction of a SG was associated with a reduction in the frequency of falls in general, particularly serious falls. Improved knowledge of research findings and how to prevent falls might improve the clinical practice regarding this issue.…”
Section: Physical Activitymentioning
confidence: 97%
“…Goto et al concluded that organized gardens can positively affect both mood and cardiac physiology of elderly individuals [137]. Gardening has also been identified as a potential activity to incorporate into fall prevention programs as gardeners reported significantly better balance and gait speed and had fewer chronic conditions and functional limitations than nongardeners [138]. However, both Kwak et al [139] and Larner [140] have also suggested that many cognitive abilities may be required for successful gardening and horticultural activities and that if gardening is being considered as a component for intervention and therapy for dementia patients, an individual approach that is customized to abilities and deficits and the various symptoms may be required.…”
Section: How Does Your Garden Grow? Definitions History and Purpmentioning
confidence: 99%
“…Park et al (2009) reported that older gardeners who met physical activity recommendations for health through gardening, e.g., at least 30 min of moderateintensity physical activity on most days of the week, showed higher overall physical health and hand functional ability (grip strength and pinch force) than older nongardeners. Persons who perform gardening tasks also had fewer chronic diseases and physical functional limitations (Armstrong, 2000;Chen and Janke, 2012). Moreover, weight-bearing gardening motions, such as body movements that work Table 1.…”
Section: Introductionmentioning
confidence: 99%